TNF signaling maintains local restriction of bacterial founder populations in intestinal and systemic sites during oral Yersinia infection - Stefan T. Peterson; Katherine G. Dailey; Karthik Hullahalli; Daniel Sorobetea; Rina Matsuda; Jaydeen Sewell; Winslow Yost; Rosemary O'Neill; Suhas Bobba; Nicolai Apenes; Matthew E. Sherman; George I. Balazs; et al. (mBio, 2025)
ABSTRACT Enteroinvasive bacterial pathogens are responsible for an enormous worldwide disease burden that critically affects the young and immunocompromised. Yersinia pseudotuberculosis is a gram-negative enteric pathogen closely related to the plague agent Y. pestis that colonizes intestinal tissues, induces the formation of pyogranulomas along the intestinal tract, and disseminates to systemic organs following oral infection of experimental rodents. Prior studies proposed that systemic tissues were colonized by a pool of intestinal replicating bacteria distinct from populations within Peyer’s patches and mesenteric lymph nodes. Whether bacteria within intestinal pyogranulomas serve as the source for systemic dissemination and the relationship between bacterial populations within different tissue sites is poorly defined. Moreover, the host factors that regulate Yersinia colonization and dissemination are not well understood. Here, we demonstrate using sequence tag-based analysis of microbial populations in R (STAMPR) that remarkably small founder populations independently colonize intestinal and systemic tissues. Notably, intestinal pyogranulomas contain clonal populations of bacteria that are restricted and do not spread to other tissues. However, Yersinia populations are shared among systemic organs and the blood, suggesting that systemic dissemination occurs via hematogenous spread. Finally, we demonstrate that TNF signaling is a key contributor to the bottlenecks limiting both initial colonization and subsequent dissemination of orally acquired bacterial populations. Altogether, this study reveals previously undescribed aspects of infection dynamics of enteric bacterial pathogens.IMPORTANCEDissemination of bacteria following intestinal infection can lead to severe disease, including sepsis, organ damage, and death. However, the intestinal bacterial population dynamics governing the colonization of mucosal and systemic tissues and the intestinal sites that seed systemic spread are not clear. Yersinia pseudotuberculosis is a rodent and human intestinal pathogen closely related to the plague agent and provides a natural rodent-adapted model to study systemic bacterial dissemination. Our findings define the infection dynamics of enteric Yersinia and the impact of the innate immune system on Yersinia colonization of the intestine and systemic organs.